New and Extended Results On Fourth-Order Differential Subordination for Univalent Analytic Functions - Atshan, Waggas Galib; Hussein Battor, Ali; Abaas, Abeer Farhan; Irina Oros, Georgia (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper, we introduce new concept that is fourth-order differential subordination and superordination associated with linear operator for univalent analytic functions in open unit disk. Here, we extended some lemmas. Also some interesting new results are obtained.